Liquidity impact on assets pricing in the context of Fama and French model. (16th January 2020) - Haddad, Ghlama; Hellara, Slaheddine
The three-factor asset pricing model of Fama and French (1993) was developed as a response to the CAPM limits in explaining the financial asset's return. However, these two models do not take into account that the liquidity factor has consistently proven to have a crucial importance. Therefore, in this research, we study the impact of liquidity on financial assets pricing in presence of Fama and French factors (SMB and HML). We use data of two portfolios of assets listed on the São Paulo and Shanghai stock exchanges, over a period of ten years, spreading between January 2003 and December 2012. Our results confirm previous studies in developed markets, and we have shown that liquidity has a significant and negative impact on the expected returns of financial assets listed on emerging markets.